Profit sharing, wage formation and flexible outsourcing under labor market imperfection - Erkki Koskela; Jan König (Institute for the Study of Labor (IZA), 2010)
We combine profit sharing and outsourcing, if the wage for worker is decided by a labor union to analyze how does the implementation of profit sharing affect individual effort and the bargained wage and thus outsourcing? We find that profit sharing and the wage level have an individual effort-augmenting effect and therefore increase productivity. We also find that the wage effect of profit sharing is ambiguous. There is a wage decreasing substitution effect, but on the other hand, there is a wage increasing effect via labor demand elasticity so that outsourcing and employment effects are also ambiguous.
Keywords: E23; E24; J23; J33; J82; 330; Flexible outsourcing; profit sharing; employee effort; labor market imperfection; Outsourcing; Erfolgsbeteiligung; Dualer Arbeitsmarkt; Lohnstruktur; Leistungsanreiz; Theorie